Value added wheat through applied genomic prediction : a genomic approach for breeding low gluten epitope wheat : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Breeding and Genetics at Massey University, Palmerston North, New Zealand - Macalister, Jamie (Massey University, 2023)
Gluten epitopes are known to trigger coeliac disease (CD) in affected consumers and are believed to be linked to some cases of gluten intolerance. Research suggests that if consumers were exposed to wheat with reduced concentrations of gluten epitopes, the incidence of CD and gluten intolerance may be reduced. Methods have recently been developed allowing researchers to measure gluten epitope concentrations in wheat. This offers wheat breeders the potential to select towards varieties with lower epitope concentrations than existing cultivars. However, the methods for measuring epitope concentrations remain costly and time consuming. Therefore, it is proposed that a genomic based approach for breeding low epitope wheat lines is a more practical method than traditional phenotype-based selections. The genetic factors associated with epitope concentrations remain poorly understood. In this thesis, heritability estimates of between 0.37-0.93 are reported for concentrations of 6 distinct gluten epitopes. The associations between epitope concentrations and baking quality are also assessed and are shown to range from being near zero for some epitopes to strong positive correlations between other epitopes and particular baking quality characteristics. A Genome Wide Association Study and a model for genomic prediction are employed to determine the genetic factors associated with epitope concentrations. In these analyses, 3 significant genomic windows are identified as being associated with concentrations of 3 particular epitopes. Empirical prediction accuracies of between 0.16-0.53 are observed for predictions of epitope concentrations in a breeding population. Additionally, accuracies of between 0.37-0.67 are achieved by adjusting the population structure to represent the ideal circumstances that breeders would aim to achieve in their training and target populations. These results demonstrate that genomic selection (GS) will be an effective method for breeding low gluten epitope wheat. The outcome of this thesis will allow implementation of GS in the New Zealand Institute for Plant & Food Research wheat breeding program where epitope concentrations will be established as a new breeding target. This is expected to lead to the release of niche, low epitope cultivars with a value-add component that benefits growers, industry and consumers.
Keywords: Wheat; Breeding; Varieties; Genetics; Gluten; Antigenic determinants; Celiac disease; gluten epitopes; genomic prediction; 300406 Crop and pasture improvement (incl. selection and breeding)